The Effect Of Regional Financial Accounting Systems, Internal Control Systems And The Role Of Internal Auditors On The Quality Of Financial Statements (Study on Regional Apparatus Organizations of Jambi Province) - Siburian, Moria Norberta; Wahyudi, Ilham; Erwati, Misni (Faculty of Economics and Business Universitas Jambi, 2023)
The purpose of this study is to examine the influence of the regional financial accounting system, internal control system, and the role of internal auditors on the quality of financial reports within the Jambi Province Regional Apparatus Organization. The research was conducted across various government offices by involving financial administration officers and expenditure treasurers as respondents. Data were collected using a questionnaire and analyzed through linear regression techniques with the support of statistical software. The findings indicate that both the regional financial accounting system and the role of internal auditors have a significant impact on improving the quality of financial reporting. Conversely, the internal control system does not show a notable influence. These results imply that enhancing accounting systems and empowering internal audit functions can contribute meaningfully to better financial governance in regional institutions.